Tax System of Hungary and its Impact on Macroeconomic Competitiveness - Nagy, Ádám; Bič, Josef; Mammadov, Orkhan; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The thesis focuses on finding the impact of the tax system of Hungary on its macroeconomic competitiveness. The first part presents the various views on macroeconomic competitiveness as a concept, followed by the introduction of taxation theory. Later, the relationship between these two elements is presented. In the second part, the political-economic development of Hungary since the fall of communism is introduced to provide context about the policies of the successive Orbán governments since 2010. In the last part, the thesis topic is researched, while analysing the tax system in the context of the main taxes, special and windfall taxes and finally certain tax benfits. It is concluded that some parts of the tax system are set up optimally, helping macroeconomic competitiveness, but are outweighed by the numerous negative elements, which hinder growth in various areas.
Vedoucí práce: Josef Bič
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses